Transport Phenomena in Novel Energy Materials – Pits and Traps in the Impedance Analysis of Ionic Conductors - Eckhardt, Janis Kevin; Justus Liebig University Giessen (My University, 2023)
Mitigating the global consequences of climate change is one of the biggest challenges of our time. The transition from fossil fuels to renewable energy sources seems to be an important milestone on the road to climate neutrality and sustainability. In this context, energy storage technologies such as secondary batteries are of great interest. This applies not only to the transformation of the automotive sector, where internal combustion engines are gradually being replaced by electric ones, but also to the storage of excess energy from renewable sources. The realization of novel electrochemical storage systems appears to be essential in this regard. Solid-state batteries with reversible metal anodes, for example, theoretically enable a much higher energy storage capacity than conventional lithium-ion batteries. However, there are still a number of challenges to overcome before this technology is ready for the market. Electrochemical impedance spectroscopy is a powerful tool for characterizing the electric transport properties of novel materials and monitoring systems in operation. It is therefore an important analysis method in the study of current and future energy storage systems. The analysis of impedance data mostly involves pattern recognition and fitting with a simple electric equivalent circuit model. This has become the standard for studying homogeneous systems such as liquids or single crystals. The analysis of inhomogeneous solid-state systems, such as polycrystalline electroceramics, porous materials, or multi-component composites, is much more complex. This is due to the microstructure of the sample and the morphology of interfaces, which introduce additional degrees of freedom into the system. As a result, the transport behavior through real structures cannot be adequately described by one-dimensional models. However, this is usually overlooked in impedance analysis in terms of material-specific properties and the transport processes taking place in the system. Therefore, the possible gain of knowledge about the system under study is limited a priori, as is the validity of the conclusions that can be drawn. The extent to which geometric effects affect the correlation between the macroscopic impedance response signal and microscopic transport or structural properties is not yet fully understood. The dissertation project explores these open questions in the context of current challenges in the development of solid-state batteries. This includes studying the effect of the solid electrolyte separator microstructure on ion transport and its effect on the material-specific transport parameters derived using the standard impedance analysis procedure. In addition, the consequences of the electrochemical and morphological (in)stability of the interface between parent metal anode and solid electrolyte separator (during operation) on the properties of the system have been analyzed in detail. To this end, a comprehensive modeling workflow has been developed that includes the generation of realistic model structures, the modeling of ion transport on the microscopic and mesoscopic scale using a multidimensional electrical network model, and automated impedance analysis. The insights gained in various studies are a significant contribution to a better understanding of the internal processes in solid-state batteries. An important finding is that the material-specific transport quantities derived with one-dimensional models sometimes exhibit inaccuracies of several orders of magnitude. It has also been shown that the impedance response of the system contains signatures of the sample geometry, such as microstructure or interface morphology, that cannot be adequately represented in one-dimensional models, leading to misinterpretations. This has been particularly evident when studying the interface behavior between lithium metal anode and garnet-type solid electrolyte: Geometric constriction effects due to morphological instabilities dramatically degrade system performance. For a long time, this has been mistakenly attributed to the charge transfer reaction, leading to the misconception that an inherently high transfer resistance prevents the realization of the reversible metal anode concept. Overall, detailed theoretical investigations have allowed to estimate structural inaccuracies of the determined transport quantities and to develop a guideline for the interpretation of experimental impedance data of parent metal anodes. The dissertation as a whole emphasizes the importance of comprehensive structural analysis when considering and interpreting solid-state systems.
Keywords: ddc:500; ddc:530; ddc:540